EFFECT OF POTENTIAL MEDICINAL PRODUCT ANTI-INFLAMMATORY AND ANTIMICROBIAL ACTIVITY ON THE FATTY-ACIDIC COMPOSITION OF THE VAGINE TISSUE AND BLOOD SERUM OF RATS WITH EXPERIMENTAL VAGINITIS - Onyshchuk, L.V. (The Ukrainian Scientific Medical Youth Journal, 2018)
The purpose of the study was to investigate the effect of a potential combined drug with antimicrobial and antiinflammatory activity on the fatty acid composition of lipids in vaginal tissue and blood serum of rats with simulated vaginitis. Materials and methods. The study was conducted on 35 female rats of the Vistar line weighing 180-220 g. Animals were divided into 5 groups: 1 – intact animals, control; 2 –animals with simulated traumatic vaginitis (TV); 3 – TV + base for suppository; 4 – TV + study drug with antiinflammatory and antimicrobial activity in the form of vaginal suppository; 5 – TV + comparative product Neo-Penotran® (“Ekselstix Helske SL”, Spain) in the form of a vaginal suppository. The study drug contained ibuprofen, clotrimazole and metronidazole in the form of suppositories. Composition Neo-Penotran® contains miconazole and metronidazole. Basis of the both medicines was the same – Vitepsol. Determination of the fatty acid composition of lipids in the tissues of the vagina and serum was carried out using the gas chromatography method. The results revealed 9 of the most informative fatty acids: of them meristic C14:0, pentodecan C15:0, palmitinic C16:0, stearic C18:0 related to saturated fatty acids (SFAs), and oleinic C18:1, linoleic C18:2, linolenic C18:3, arachidonic C20:4, which is the sum of unsaturated fatty acids (UFAs). Linoleic C18:2, linolenic C18:3, arachidone C20:4 LC are part of polyunsaturated fatty acids (PUFAs) and are characterized as essential. Conclusions. The study results showed that there is a change in the total content of SFA, UFA and PUFA in the background of traumatic vaginitis: SFAs – 44.5%, UFA – 55.5% and PUFA – 31.9% versus 50.4%, 49.6% and 27.5% of lipids in the vaginal tissue in the control group. It was found that after administration of the study drug against the background of traumatic vaginitis, the normalization of the SFA ratio was 37.8%, the UFA 62.2%, and the PUFA – 44.4% compared to 43.3%, 56.7% and 35.4% serum lipids in the control pathology.